Comprehensive energy and exergy analysis on optimal design parameters of recuperative supercritical CO2 power cycle - Bashan, Veysi; Gumus, Emrah (INDERSCIENCE ENTERPRISES LTD, 2018)
This paper focuses mainly on the supercritical carbon dioxide (s-CO2) cycles performance as regards from the aspect of thermodynamic point of view. Detailed analyses have been performed by considering; the effects of compressor inlet temperature and pressure, turbine inlet temperature, compressor outlet pressure, recuperator pinch temperature and pressure drop. Turbine and compressor efficiencies on cyclic performance were investigated and the results have been given. Exergy efficiency and exergy destruction ratios have been provided with respect to compressor inlet temperature variation. Exergy efficiency decreased when compressor inlet temperature increased. Results show that an optimum input pressure value for high cycle efficiency should be a value between 75 bar and 90 bar. In addition, the pressure ratio should be between 2.5 and 3 in order to have high cycle efficiency and high output power. The effect of the increase in turbine efficiency is more important than compressor efficiency.
Keywords: Brayton cycle; supercritical; s-CO2; thermodynamic analysis; exergy; DIOXIDE BRAYTON CYCLE; WASTE HEAT-RECOVERY; CARBON-DIOXIDE; SOLAR-ENERGY; DRIVEN; OPTIMIZATION; GENERATION; GAS; TEMPERATURE; SYSTEM; Thermodynamics; Energy & Fuels